用于治疗血细胞减少症或减少血细胞减少症的持续时间的佛波醇酯组合物和方法 (2022)
提供了用于治疗哺乳动物受试者的血细胞减少症的的方法和组合物，其包含与G-CSF组合或与EPO组合的佛波醇酯或佛波醇酯的衍生物。该组合物和方法也减少血细胞减少症如中性粒细胞减少症、血小板减少症和/或贫血症的持续时间。 Methods and compositions containing a phorbol ester or a derivative of a phorbol ester in combination with G-CSF or in combination with EPO, are provided for the treatment of cytopenia in mammalian subjects. The compositions and methods also reduce the duration of cytopenia such as neutropenia, thrombocytopenia, and/or anemia.